Biportal endoscopic decompression, debridement, and interbody fusion, combined with percutaneous screw fixation for lumbar brucellosis spondylitis - Wang, Xiangbin; Long, Yubin; Li, Yong; Guo, Yun; Mansuerjiang, Maiwulan; Tian, Zheng; Younusi, Aikebaier; Cao, Li; Wang, Chong (Frontiers in Surgery, 2023)
Objective This study aims to investigate the effectiveness and feasibility of biportal endoscopic decompression, debridement, and interbody fusion, combined with percutaneous screw fixation for lumbar brucellosis spondylitis (LBS). Methods The data of 13 patients with LBS were retrospectively analyzed, who underwent biportal endoscopic decompression, debridement, and interbody fusion, combined with percutaneous screw fixation from May 2020 to June 2022. The patients’ clinical data, the duration of operation, the estimated blood loss (including postoperative drainage), and complications were recorded. Clinical outcomes include serum agglutination test (SAT) measures Brucella antibody titer, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), the visual analog scale (VAS) scores of low back and leg, Japanese Orthopaedic Association (JOA) score, Oswestry Disability Index (ODI), American Spinal Injury Association neurological classification, and lordotic angle were analyzed. All patients were assessed using the modified Macnab criteria at the final follow-up. The intervertebral bone graft fusion was assessed using the Bridwell grading criteria. Results The mean operation duration was 177.31 ± 19.54 min, and the estimated blood loss was 176.15 ± 43.79 ml (including postoperative drainage was 41.15 ± 10.44 ml). The mean follow-up period was 13.92 ± 1.5 months. SAT showed that the antibody titers of 13 patients were normal 3 months after the operation and at the final follow-up. ESR and CRP levels returned to normal by the end of the 3-month follow-up. VAS scores of low back and leg, JOA score, and ODI significantly improved after the operation throughout the follow-up period (P < 0.05). Based on the modified Macnab criteria, 92.3% showed excellent to good outcomes. One patient had only a percutaneous screw internal fixation on the decompression side due to severe osteoporosis. One case suffered a superficial incision infection postoperatively that healed with dressing change and effective antibiotic treatment. Bony fusion was obtained in all patients at the last follow-up, including 12 cases with grade I and 1 case with grade II, with a fusion rate of 92.31%. Conclusion Biportal endoscopic decompression, debridement, and interbody fusion, combined with percutaneous screw fixation is an effective, safe, and viable surgical procedure for the treatment of LBS.